2016
DOI: 10.1590/0101-60830000000077
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between major depressive disorder and ACE gene I/D polymorphism in a Turkish population

Abstract: Background: Major depressive disorder (MDD) is a complex disease and a significant health problem that is prevalent across the world. Angiotensin-converting enzyme (ACE) has an important role in renin-angiotensin system (RAS) and converts inactive angiotensin I to a potent vasopressor and aldosterone-stimulating peptide angiotensin II. Levels of ACE in plasma vary according to the insertion/deletion (I/D) polymorphism of ACE gene. Objective: The aim of the current study was to examine the influence ACE gene I/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
3
2
0
Order By: Relevance
“…ACE genotype distribution differs from one population to another or even from one year to another in the same population. In Palestine, the D/D genotype was the most frequent genotype as demonstrated by the present study and this result is also similar to other studies [8,12], as it was shown to be the most frequent genotype in Iraq [13], while the I/D genotype was the most frequent genotype in Turkey [14] and the UAE [6]. Some countries like Egypt [15,16] have an inconstant frequency for the genotypes, and this may be related to the sample size, the population of the study or the techniques used in the determination of ACE gene polymorphism.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…ACE genotype distribution differs from one population to another or even from one year to another in the same population. In Palestine, the D/D genotype was the most frequent genotype as demonstrated by the present study and this result is also similar to other studies [8,12], as it was shown to be the most frequent genotype in Iraq [13], while the I/D genotype was the most frequent genotype in Turkey [14] and the UAE [6]. Some countries like Egypt [15,16] have an inconstant frequency for the genotypes, and this may be related to the sample size, the population of the study or the techniques used in the determination of ACE gene polymorphism.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of the association with HTN, it was not deemed to be statistically significant, and this result concurs with [8] and [14] but disagrees with Alsafar et al (2015) [6]. D/D genotype…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The DD genotype and D allele may serve as the criteria for identifying patient groups which are at high risk for MI and CHD [56]. A studies conducted in Iraq [53], Algeria [45] and Lebanon [47] showed that there was statistically significant between ACE genotype among the study groups which differ from our findings, while there was good agreement between our results and the results that revealed from Turkish one [49]. No significant differences were detected in allele or genotype frequencies between patients and controls (p = 0.48).…”
Section: Relationship Between Chd and Ace Gene Polymorphismsupporting
confidence: 62%
“…There were no allele frequency differences between Turkish control women and women with COVID-19 for the ACE I/D. [28][29][30] The ACE2 gene is located on the X chromosome at the position Xp22. It contains 18 exons and shows close homology to ACE gene, since ACE2 discovered as a homolog of ACE.…”
Section: Serpine1 (Pai-1)mentioning
confidence: 91%